PENGHITUNGAN EMISI KARBON DARI LIMA SEKTOR PEMBANGUNAN BERDASAR METODE IPCC DENGAN VERIFIKASI FAKTOR EMISI DAN DATA AKTIVITAS LOKAL - Purwanta, Wahyu (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
After ratifying the Kyoto Protocol, Indonesia has obligation to make report on NationalÃ‚Â GHGs emission for UNFCCC. There are some studies at national level related to GHGsÃ‚Â inventory. In this study we calculated GHG (CO2 and CH4) emissions from 5 (five) sectorsÃ‚Â i.e forestry, energy, industry, agriculture and waste. Calculation use 2006 IPCC methodÃ‚Â with local values for verification or enhanced the Tier of method. The local values are,Ã‚Â forestry allometric equation, emission factor of paddy field, generation and compositionÃ‚Â of municipal solid waste, solid waste management as well. Calculation result of GHGsÃ‚Â emission in this study is 827,058 Gg/year in the term of CO2 equivalent. This numbers isestimated arround 60% of the realistic numbers due to the accuracy of the transportationÃ‚Â data and unaccounted peat fire data in the study. Carbon emission from peat fire is theÃ‚Â biggest emission. From all sector has calculated, forestry sector is the biggest CO2eÃ‚Â emmitor with contribute arround 58%, follow energy sector (25%), agriculture (8% ),industry sector (6%), and waste sector (3%). The proportion of distribution each sectorÃ‚Â can change if the data more broad the calculation include more detail in sub sectors.Key words : GHGs Emissions, Local Values, Sector Contribution